Effects of a three-lobe swirl generator on the thermal and flow fields in a heat exchanging tube: An experimental and numerical approach. (15th September 2017) - Jafari, Mohammad; Dabiri, Sadegh; Farhadi, Mousa; Sedighi, Kurosh
Highlights: A new type of swirl generator is proposed for enhancing heat transfer in a tube. The swirl generator is a helically twisted tube with a three-lobbed cross section. The heat transfer rate and pressure drop are experimentally studied. The thermal performance varies in a range 1.25–1.55 for different swirl generators. The experiments are accompanied with numerical simulations to understand the details of swirl flow. Abstract: The current experimental study primarily focuses on the effects of an injected swirling flow on the thermal performance of the test tube. The swirl generator is a helically twisted tube with a three-lobe cross section. To evaluate the thermal performance of the test tube equipped with the swirl generator, the Nusselt number and the friction factor are considered as the target outcomes. The study is carried out for different values of twist-angle ( 90 ⩽ θ ⩽ 360 ) and length ( 1 ⩽ l ⩽ 4 ) as the main geometrical parameters of the swirl generator, and the Reynolds number varies from 5000 to 30000. The experimental study is accompanied by a comprehensive Large Eddy Simulation (LES). The generated swirling flow and its dissipation rate along the test tube are numerically investigated in details. The numerical results clarify the potential of the swirl generator to enhance the convection rate. The Smagorinsky approach is used to model the effects of the sub-grid scales on the flow field. The simulation is performed using an open-source CFD code named OpenFOAM. The results show that the swirl generator leads to a significant enhancement in Nusselt number accompanied by an acceptable increase in the friction factor.